(untitled) - Barzun, Jacques (New York, 1977)
This classic introduction to the techniques of research and the art of expression is used widely in history courses, but is also appropriate for writing and research methods courses in other departments. Barzun and Graff thoroughly cover every aspect of research, from the selection of a topic through the gathering, analysis, writing, revision, and publication of findings presenting the process not as a set of rules but through actual cases that put the subtleties of research in a useful context. Part One covers the principles and methods of research; Part Two covers writing, speaking, and getting one's work publishedne of the earlier hardcover editions of this manual on writing and its various styles
Keywords: Historiography,Biên soạn lịch sử,Academic writing,Viết bài nghiên cứu